EFFECTIVE STRATEGIES FOR TEACHING LEGAL ENGLISH: FOCUS ON INTERNATIONAL CONTEXTS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This article explores effective approaches to teaching legal English, emphasizing the global demands of the legal profession. It highlights the use of real-life cases from international law and role-playing techniques such as trial simulations and negotiation exercises. These strategies not only help students master complex legal terminology but also foster critical thinking, argumentation, and intercultural communication skills. By integrating these methods into the curriculum, educators can better prepare students for successful careers in international legal environments.